SYMMETRIC KEY STREAM CIPHER CRYPTOGRAPHIC METHOD AND DEVICE - DOMOSI, Pal Bela; HORVATH, Geza (2020)
The subject of the invention is a symmetric key stream cipher cryptographic method for encrypting plaintexts and decrypting ciphertexts during which process a text to be encrypted or an encrypted text is scanned with an input/output data buffer (5), a pseudo random number is created with a pseudo random number generator (8) with a seed (12), a key automaton (11) is used for encryption and/or decryption. It is characterized in that the procedure involves the method whereby using the characters of the text scanned by the input/output data buffer (5) and the pseudo random number generated by the pseudo random number generator (8), an element of the key automaton's (11) transition matrix is directly reached from the input/output data buffer (5); the procedure is then repeated. A symmetric key stream cipher cryptographic device for implementing the method of claim 1 is also the subject of the invention.